THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE SYSTEM EDUCATION - Shukurov Shuxrat Zayniyevich (European Science Publishing, 2024)
Today, artificial intelligence (AI) is present in numerous aspects of society, with its influence expanding rapidly. AI is increasingly being applied in various fields, including education. Defined as a branch of science in which machines, particularly computers, perform tasks that typically require human intelligence, AI focuses on enhancing human-machine interactions through technologies like smart systems, natural language processing, speech recognition, and machine vision. Globally, the demand for AI is on the rise. From real estate to digital marketing, AI has transformed numerous industries, and education is no exception. It plays a significant role in teaching and learning processes. Currently, schools and universities are incorporating AI to refine their teaching approaches and achieve better outcomes. This paper discusses the significance of artificial intelligence in the field of education.
Keywords: artificial intelligence, AI, the Internet, education, machine learning, educational data mining, algorithm.